Significant differences between Crohn’s disease and ulcerative colitis regarding the impact of body mass index and initial disease activity on responsiveness to azathioprine: results from a European multicenter study in 1,176 patients - Holtmann, Martin; Krummenauer, Frank; Claas, Christina; Kremeyer, Kristina; Lorenz, Dirk; Rainer, Olivia; Vogel, Iris; Böcker, Ulrich; Böhm, Stephan; Büning, Carsten; Duchmann, Rainer; Gerken, Guido; et al. (Digestive diseases and sciences, 2010)
In a survey comprising 1,176 patients with inflammatory bowel disease (IBD) we recently showed that azathioprine (AZA) beyond 4 years is beneficial in ulcerative colitis (UC) patients and in a subset of Crohn’s disease (CD) patients. Here, we show for the first time that azathioprine responsiveness depends on body mass index (BMI). The relationship is reciprocal in UC and CD, with a better outcome in UC patients with a BMI<25 and in CD patients with a BMI>25. These observations are particularly interesting considering the evolving concept of a relationship between fatty metabolism and immune regulation. Additionally, we show that CD patients, but not UC patients, respond better to AZA when it is started in clinical remission. This observation may support data favouring a “hit hard and early” regime in CD. Finally, we were able to demonstrate a decrease in the incidence of CD-related complications requiring surgery through treatment with AZA.
Published: 10 June 2009
Gesehen am 17.03.2023